Questionnaire for the Assessment of Optimism: Reliability and Evidence of Validity [Cuestionario Para la Evaluación del Optimismo: Fiabilidad y Evidencias de Validez] - Celis-Atenas, K (Sociedad Chilena de Psicologia Clinica, 2015)
Optimism has been shown to have numerous physical and emotional benefits in a range of populations and professional contexts. Nonetheless, there are few instruments for its evaluation and they have significant limitations, especially in young people. This work presents a questionnaire which, through 9 items, evaluates dispositional optimism and analyses its relationship to personality and emotional intelligence. The sample was made up of 2,963 Spanish adolescents of whom 51.10% were male. Emotional intelligence was measured using the Trait Meta-Mood Scale-24, while the big-five personality traits were measured using the Overall Personality Assessment Scale. The optimism questionnaire demonstrated high reliability (α=.84), it was accurate over a wide ability range (θ from -3 to +2) and gave an acceptable fit to a unidimensional structure. The clear relationship between optimism, personality traits and emotional intelligence was confirmed. © 2015 by Sociedad Chilena de Psicología Clínica.